2015
DOI: 10.1002/lom3.10003
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for the measurement of CO2 and CH4 emissions from surface water reservoirs: Results from an international workshop held at Three Gorges Dam, June 2012

Abstract: Fluxes of carbon dioxide (CO2) and methane (CH4) from hydroelectric and water supply reservoirs are receiving increasing attention around the world with a number of research groups having undertaken measurements of these emissions across a range of lakes and reservoirs located in different climates and landscapes. The use of floating chambers (aka flux chambers) is the most common technique for direct measurement of these fluxes. However, the relative performance of different measurement systems, especially di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…We calculated the daily (from 10 am to 4 pm) average and the standard error from these measurements. We obtained the flux calculation using the equation (1) (Zhao et al 2015):…”
Section: Quantification Of Co 2 Ch 4 and N 2 O Fluxesmentioning
confidence: 99%
“…We calculated the daily (from 10 am to 4 pm) average and the standard error from these measurements. We obtained the flux calculation using the equation (1) (Zhao et al 2015):…”
Section: Quantification Of Co 2 Ch 4 and N 2 O Fluxesmentioning
confidence: 99%
“…Zhao et al. () suggested such a method as a tool for assessing diffusion and ebullition, while Grasset et al. () was one of the first studies to include ebullition data from these newer gas analysers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when no linear regression trend was observed to determine the flux, we used the initial and end points to determine the sum of diffusive and ebullitive CH 4 fluxes, as discussed by Goodrich, Varner, Frolking, Duncan, and Crill (2011), Zhao et al (2015) and Grasset, Abril, Guillard, Delolme, and Bornette (2016). We acknowledge that our sampling procedure may not accurately measure diel gas emissions, as previous studies have found large variations in diel CH 4 and CO 2 fluxes (Liu et al, 2016;Natchimuthu, Selvam, & Bastviken, 2014;Natchimuthu et al, 2016).…”
Section: Greenhouse Gas Flux Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, studies on buoyant and sinking phytoplankton could continue with a focus on the intensity of water mixing in interaction with its timing and duration (Huisman et al 2002;Huisman et al 2004;Blottière et al 2014;Zhou et al 2015). Sixth, gas dynamics in the water column and gas exchanges at the air-water interface are of major importance to understand freshwater community dynamics (see for instance Verspagen et al 2014;Hanson et al 2015;Zhao et al 2015). Gas exchanges between the atmosphere and water depend on wind velocity and wave height among other parameters (Vachon and Prairie 2013).…”
Section: Discussionmentioning
confidence: 99%